Low energy intensity production of fuel-grade bio-butanol enabled by membrane-based extraction. Issue 12 (30th October 2020) - Kim, Ji Hoon; Cook, Marcus; Peeva, Ludmila; Yeo, Jet; Bolton, Leslie W.; Lee, Young Moo; Livingston, Andrew G.
Abstract : Innovative membrane-based extraction system tailoring affinity-driven separation enables continuous biodiesel production with high productivity and low energy consumption. Abstract : Widespread use of biofuels is inhibited by the significant energy burden of recovering fuel products from aqueous fermentation systems. Here, we describe a membrane-based extraction (perstraction) system for the recovery of fuel-grade biobutanol from fermentation broths which can extract n -butanol with high purity (>99.5%) while using less than 25% of the energy of current technology options. This is achieved by combining a spray-coated thin-film composite membrane with 2-ethyl-1-hexanol as an extractant. The membrane successfully protects the micro-organisms from the extractant, which, although ideal in other respects, is a metabolic inhibitor. In contrast to water, the extractant does not form a heterogeneous azeotrope with n -butanol, and the overall energy consumption of for n -butanol production is 3.9 MJ kg −1, substantially less than other recovery processes (17.0–29.4 MJ kg −1 ). By (a) extracting n -butanol from the fermentation broth without a phase change, (b) breaking the heterogeneous azeotrope relationship (less energy consumption for distillation), and (c) utilizing a small volume ratio of extractant : fermentation broth (1 : 100, v/v), the need for high energy intensity processes such as pervaporation, gas stripping or liquid–liquid extraction is avoided. The application of this perstraction system to continuous production of a range of higher alcohols is explored and shown to be highly favourable.